2013
DOI: 10.1111/jgs.12411
|View full text |Cite
|
Sign up to set email alerts
|

Does Reducing Length of Stay Increase Rehospitalization of Medicare Fee‐for‐Service Beneficiaries Discharged to Skilled Nursing Facilities?

Abstract: Background/Objectives Rehospitalizations are costly and pose risks for patients. Increased rates of rehospitalization have accompanied decreases in hospital length of stay, raising the possibility that these two trends are causally related. Our objective was to analyze the relationship between length of stay and rehospitalization. Design Retrospective cohort study. Setting 6,537 hospitals nationwide from January 1999 through September 2005. Participants Medicare fee-for-service beneficiaries associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…For cardiovascular disease as a whole, some large studies have been reported, mostly positive [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], although longer term translation of findings into actual clinical care within those systems is unknown.…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 99%
“…For cardiovascular disease as a whole, some large studies have been reported, mostly positive [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], although longer term translation of findings into actual clinical care within those systems is unknown.…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 99%
“…Patients and hospitals with longer length of stay showed reduced readmission rate in HF patients [37]. Alternatively, individuals hospitalized for heart failure, had no increase in 30-day re-hospitalization when LOS was decreased by a day [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…8,9 Twenty-two percent of Medicare beneficiaries experience such an event during a PAC stay, of which more than half (59%) are preventable. 9 For short-stay patients, such an event often leads to a rehospitalization, 9–11 which may limit their ability to achieve their goal of returning to the community; however, no study has systematically looked at the achievement of this rehabilitation outcome.…”
Section: Introductionmentioning
confidence: 99%